أوصاف الجنة والنار في القرآن الكريم - العقيل، ليلى بنت محمد بن سليمان (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2022)
هدف البحث إلى التعريف بكل من الجنة والنار، وبأسمائهما الواردة في القرآن الكريم، كما هدف إلى بيان عدد من أوصاف الجنة التي وردت في القرآن الكريم، وتعليق المفسرين عليها، إضافة إلى بيان عدد من أوصاف النار الواردة في القرآن الكريم، وأقوال المفسرين فيها. واستخدمت البحث المنهج الاستقرائي، وهو المنهج الذي يعتمد بشكل كبير على ملاحظة المتعلم، إذ يتم تقديم مجموعة من الأمثلة من قبل المعلم تتيح للطالب القدرة على استنتاج كيفية عمل المفهوم، وذلك من خلال الملاحظة والقدرة بعدها على تحديد القواعد المرتبطة بذلك المفهوم. وقد أسفر البحث عن عدد من النتائج أهمها: - للجنة أسماء متعددة وردت في القرآن الكريم على سبيل تشويق المؤمنين إلى دخول الجنة، والعمل بما يقربهم من الجنة، وما يسكنهم في الدرجات العليا من الجنة. - كما وردت أسماء للنار في القرآن الكريم، الغرض منها تخويف العاصين وترهيبهم مما سيؤول إليه حالهم إذا استمروا في معاصيهم، وفيها أيضا زجر للكفار وتنبيها لهم على خطأ معتقدهم، وأن مآلهم إلى النار إذا لم يؤمنوا بالله الواحد القهار. - للجنة درجات كثيرة ومتعددة، والدرجات بداخلها درجات أخرى يسكنها المؤمنون بالله بحسب أعمالهم في الدنيا، كما أن للجنة دركات بعضها تحت بعض، يسكن أسفلها المنافقون. - أن أوصاف الجنة والنار كثيرة في القرآن الكريم تحتاج إلى مجلدات للحديث عن أوصافهما والتدليل عليها. ومن التوصيات التي نوصي بها: - العمل على تقوى الله، ومجاهدة النفس وكيد الشيطان هو السبيل إلى الفوز بجنات النعيم، والبعد عن نيران الجحيم. The aim of the research is to introduce both paradise and fire, and their names in the Qur'an, as well as to describe a number of descriptions of paradise contained in the Qur'an, to comment on them, in addition to a number of descriptions of the fire contained in the Qur'an, and the statements of the interpreters. The research used the inductive curriculum, which is largely based on the learner's observation, as a set of examples is provided by the teacher that allows the student to conclude how the concept works, by observing and then being able to determine the rules associated with that concept. The research has yielded a number of results, the most important of which is The Committee has several names mentioned in the Holy Quran as a way to thrill believers to enter paradise, to work near them from paradise, and what dwells them in the higher grades of paradise. There are also names of fire in the Qur'an, which are intended to intimidate and intimidate the sinners, which will become their situation if they continue their sins, and also to disengreg the infidels and alert them to the mistake of their belief, and that their money is to fire if they do not believe in the one almighty God. The Committee has many and many degrees, and the degrees within it are other degrees inhabited by believers in God according to their actions in the world, and the committee has gendarmes under each other, beneath which the hypocrites live. The descriptions of paradise and fire are many in the Qur'an and need volumes to talk about and demonstrate their descriptions. Recommendations we recommend include: Working on God's piety, self-struggle and Satan's intrigue is the way to win paradises of bliss, and to stay away from the fires of hell.
Keywords: أسس العقيدة -- الجنة والنار -- أسماء النار -- أوصاف الجنة